Konflik Tanah Surat Ijo di Surabaya (Sebuah Perspektif Teoretik-Resolutif) - Sukaryanto, Sukaryanto (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
Abstract : The control/ownership of land in Surabaya is marked by the unique phenomenon of surat ijo ; many residents in the municipalities life on state land. Entering Reform Ere (1999), most of the occupants were no longer abide to the existing regulations. Furthermore, solidarity within community of “tanah surat ijo” arises, and has led them to establish their own mass organization and fight for hak milik (HM, land ownership rights) over the land they occupy. It is thus unsurprising that conflict of interest has occurred between the two. Various efforts to resolve this conflict have been undertaken, including mediation and a civil suit, but these have been unsuccessful to date. Similarly, the enactment of Peraturan Daerah No. 16 Tahun 2014 (Surabaya Municipal By law No. 16 of 2014) was unable to resolve the conflict. This paper attempts to understand and explain the context of land control, ownership, and conflict over “tanah surat ijo” in Surabaya. As conclusion, that the system of “tanah surat ijo” -is a transformation of the colonial land rent system-has affected all aspects (be they social, economic political, cultural, or psychological) of its residents lives. Besides that, to promote conflict resolution, there must be a transformation in “tanah surat ijo” system; this requires the involvement, cooperation, and coordination between relevant ministries. Keywords : surat ijo, state land, resolution, conflict, Surabaya Intisari : Penguasaan/pemilikan tanah di Surabaya ditandai fenomena unik tanah surat ijo, yakni permukiman sebagian warga kota di atas tanah negara. Memasuki era Reformasi (1999) sebagian besar warga penghuni tidak lagi patuh pada peraturan yang berlaku. Bahkan, timbul solidaritas komunitas warga pemukim tanah surat ijo yang kemudian membentuk organisasi massa melakukan upaya untuk memperoleh hak milik atas tanahnya. Tak pelak, terjadilah konflik sosial antara keduanya. Berbagai upaya resolusi telah dilakukan mulai mediasi hingga di meja peradilan tertinggi belum bisa menyelesaikan. Demikian pula, pemberlakuan Peraturan Daerah No. 16 Tahun 2014 tentang pelepasan asset pun belum dapat mewujudkan resolusi konflik. Tulisan ini mencoba untuk memahami dan menjelaskan konteks penguasaan, kepemilikan, dan konflik atas tanah surat ijo di Surabaya. Sebagai simpulan, keberadaan tanah surat ijo –sebagai jelmaan sistem sewa tanah pada era kolonialtelah menimbulkan dampak di semua segi kehidupan warga penghuni, mulai aspek sosial, ekonomi, politik, hingga budaya/ psikologi. Selain itu, di dalam kerangka upaya mencapai resolusi konflik diperlukan perubahan system tanah surat ijo, untuk itu perlu keterlibatan, kerjasama, dan koordinasi antara beberapa kementerian yang terkait. Kata Kunci: surat ijo , tanah negara, resolusi, konflik, Surabaya